Strategic entry or strategic exit? International presence by emerging economy enterprises - Sun, J.; Wang, S.; Luo, Yadong (Elsevier, 2017)
© 2017 Elsevier Ltd. By proposing an integrated strategic choice framework, we theorize the distinctive dynamics of international expansion by emerging economy enterprises. Specifically, we explicate how these firms build international presence based on combined strategic entry (i.e., prompted by internal capabilities such as innovation and diversification) and strategic exit (i.e., pushed out by external handicaps at home such as institutional obstacles and market competition). Further, a firm's cooperative ties with foreign multinationals in the former's home country fortify the strategic entry intent, while ties with home government institutions weaken the strategic exit intent. We also demonstrate that building international presence helps bolster firm performance, highlighting the economic catch-up consequence of international expansion. Analyses of a two-year imbalanced panel data of 2136 firms statistically support our hypotheses.